Case Study in Youth Flexible Assertive Community Treatment: An Illustration of the Need for Integrated Care - Broersen, Marieke; Frieswijk, Nynke; Coolen, Rob; Creemers, Daan H. M.; Kroon, Hans (Frontiers in Psychiatry, 2022)
Youth Flexible Assertive Community Treatment (Youth Flexible ACT) is a client- and family-centered service delivery model for young people up to 24 years of age who have interrelated psychiatric- and social problems across multiple life domains and do not readily engage with office-based mental health services. Youth Flexible ACT teams were set up to meet the multifaceted needs of this subgroup in an integrated manner. In this paper, we present a case study to 1) describe the core principles of Youth Flexible ACT and 2) illustrate the application of mental healthcare model. Subsequently, we describe the contribution of model elements to a positive care process and discuss the challenges of the team in working with the model. The case study displays the importance of integrated flexible and personalized care services to enable adolescents to remain engaged in care.